Challenges of Healthcare Systems in Saudi Arabia to Delivering Vision 2030: An Empirical Study From Healthcare Workers Perspectives - Al-Anezi FM (Journal of Healthcare Leadership)
Fahad M Al-Anezi College of Business Administration, Department Management Information Systems, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Fahad M Al-Anezi, Email fmoalanezi@iau.edu.saBackground and Aim: This study explores the key challenges affecting the healthcare system in Saudi Arabia as it strives to achieve the objectives of Vision 2030. Unlike previous research, which has primarily focused on policy and structural reforms, this study provides empirical insights from healthcare workers, offering a frontline perspective on the barriers to effective healthcare transformation.Methods: A cross-sectional survey was conducted among 383 healthcare professionals from public and private hospitals. The questionnaire covered challenges related to capacity and infrastructure, workforce shortages, digital transformation, preventive healthcare, coordination and integration, healthcare financing, public awareness, quality of care, and disease prevention. Data were analyzed using descriptive statistics, t-tests, and ANOVA to assess variations in perceptions based on professional roles, work experience, gender, and hospital type.Results: The findings reveal workforce shortages, infrastructure limitations, and digital transformation gaps as the most pressing concerns. Notable differences in perceptions highlight the need for tailored interventions across different healthcare roles and settings. Addressing these challenges requires strategic workforce planning, investment in infrastructure, digital innovation, and sustainable financing models.Conclusion: This study contributes to the literature by offering evidence-based recommendations for policymakers and healthcare administrators, aligning healthcare system improvements with Vision 2030 objectives. The insights provided can help shape targeted strategies to enhance healthcare efficiency, accessibility, and resilience in Saudi Arabia.Keywords: Vision 2030, Saudi Arabia, healthcare challenges, transformation, workforce, digital health, policy reform